Pola Distribusi Unggas dari Pasar Tradisonal Berperan dalam Penyebaran Virus Flu Burung - SUMA ANTARA, I MADE; SUARTHA, I NYOMAN; SAKA WIRYANA, I KADEK; SUKADA, I MADE; WIRATA, I WAYAN; DIBYA PRASETYA, I GUSTI NGURAH; RITHA KRISNA DEWI, NI MADE; KOMALA SARI, TRI; KADE MAHARDIKA, I GUSTI NGURAH (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
A study has been carried out to map the distribution pattern of poultry from traditional market toreduce the transmission risk of avian influenza virus. The data were collected from threes markets wherepoultry are sold, namely in Bringkit of Badung Regency, Kumbasari of Denpasar City, and Kediri ofTabanan Regency. Data collections was based on interviews using questionnaire. Poultry from all marketsare distributed throughout Bali. Poultry are traded mainly for religious ceremony and immediatelyslaughtered as it arrives at the consumer’s house. The distribution pattern of poultry seems to play asignificant role in the disseminations of avian influenza virus. The right implementation of biosecurity intraditional markets is highly recommended to curb the risk.
Keywords: poultry distribution pattern, traditional market, avian influenza virus